Insights into vertebrate head development: from cranial neural crest to the modelling of neurocristopathies - Weiner, Andrea María Julia (2020)
Fil: Fil: Weiner, Andrea María Julia. Universidad de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR-CONICET). Argentina.